Medicinal plants as a source of antiviral agents against dengue, chikungunya, zika and yellow fever: A narrative review (Research, Society and Development, 2025)
Arboviruses represent a growing challenge to global public health, with dengue, chikungunya, zika, and yellow fever standing out due to their epidemiological impact in tropical and subtropical regions. The control of these infections is still limited by the absence of specific antiviral therapies and the increasing resistance of vectors, reinforcing the need for new therapeutic approaches. In this context, the bioprospecting of medicinal plants has gained attention due to the antiviral potential of their secondary metabolites. This study aims to summarize the current evidence on medicinal plant species with confirmed antiviral activity against arboviruses, emphasizing their mechanisms of action. Thus, this narrative review compiled updated evidence on phytochemicals with anti-arboviral activity, describing their mechanisms of action against Dengue virus (DENV), Chikungunya virus (CHIKV), Zika virus (ZIKV), and Yellow Fever virus (YFV). The results showed that essential oils, saponins, flavonoids, alkaloids, and diterpenoid derivatives may act through virucidal activity, inhibition of viral replication, and modulation of the host cell. Therefore, plant-derived compounds represent promising alternatives for the development of innovative therapeutic agents against arboviruses transmitted by mosquitoes.